Ekonomi Syariah Sebagai Implementasi Filsafat Ekonomi Islam Dalam Mencapai Keadilan Ekonomi - Alya Arianti Nasution; Cindy Aulia Zalyanti; Wahyudin; Ahmad Wahyudi Zein (CV. ITTC INDONESIA, 2024)
The purpose of this study was to determine the Islamic economy as an implementation of Islamic economic philosophy in achieving economic justice. The building of Islamic Economics is based on the main foundation of tawhid. The next foundation is sharia and morals. The practice of sharia and morals is a reflection of tawhid. The foundation of tawhid that is not solid will result in the implementation of sharia and morals not running on the provisions of the concept of tawhid. The type of research used is qualitative data sources obtained and collected by researchers not directly, but through other parties. The benefits of Islamic economic philosophy are not just an effort to Islamize science alone, but the existence of Islamic economic philosophy contributes knowledge, ideas or basic foundations laying the sciences in general including economics and involvement in constructing human civilization, towards a better human economic civilization. The essence or ontology of Islamic economics is an economic system based on divine revelation, it not only regulates the procedure of a person in meeting his needs but also places him as a servant of Allah ta'ala.